INDICATIONS FOR AND MEDICAL-SOCIAL ASPECTS OF CAESAREAN SECTION - Zlatina Nikolova; Milena Sandeva (Journal of IMAB)
The aim of this research is to study the main medical-social aspects and indications when performing CS. For this purpose, we conducted a retrospective epidemiological study. We used a documentary method. A total of 467 deliveries through CS were covered. The group of women in the age group from 30 to 34 yrs., incl., is the largest one. 233 women in the sample have at least one born child, 178 of them have undergone at least one previous CS. In 453 cases, the pregnancy is a singleton one, while in 14 cases, the pregnancy is a twin one. There is a stated refusal of attempted vaginal delivery and insistence of the woman for delivery through CS in the cases of 32 pregnant women in the sample. They do not differ in age versus the rest of the cohort, yet higher education level is observed in their cases. We did not find any statistically significant difference in the period of postoperative stay in the group of women who stated a refusal. CS is usually indicated by a few factors. The leading indication for surgical intervention in this study is the presence of an already performed CS. This indication is almost always accompanied by at least one more indication, as most often it is low pelvic score, established labour or presence of pain in the region of the surgical cicatrix. The presence of eye pathology and evidence of a narrow pelvis are independent reasons for CS.